Being Cosmopolitan: Marketing Development Studies in the Neoliberal University. (July 2022) - Patel, Kamna
This article unpacks how 'development' is represented and sold in postgraduate development studies courses at two UK universities, based on a close reading of the course's marketing materials and interviews with professional marketing staff within the university, academic leads on development studies courses and current development studies students. It explores the effects of development representations on students and their imaginations of the discipline and the university brand. I find representations of development engender a cosmopolitan desire mainly among international students and project a cosmopolitan virtue of the university through its development activities and associations. Contrary to seeing the cosmopolitan as a progressive political concept in a time of globalisation, I contend these cosmopolitan identities are imbued with the racialised legacies of colonial power.